New species of Scissurellidae, Anatomidae, and Larocheidae (Mollusca: Gastropoda: Vetigastropoda) from New Zealand and beyond - Geiger, Daniel L.; Marshall, Bruce A. (Zootaxa, 2012)
Thirteen new species of Scissurellidae (Scissurella regalis n. sp., Sinezona mechanica n. sp., Sinezona platyspira n. sp.,Sinezona enigmatica n. sp., Sinezona wanganellica n. sp., Satondella azonata n. sp., Satondella bicristata n. sp.),Anatomidae (Anatoma amydra n. sp., Anatoma kopua n. sp., Anatoma megascutula n. sp., Anatoma tangaroa n. sp.), andLarocheidae (Larochea spirata n. sp., Larocheopsis macrostoma n. sp.) are described, all of which occur in New Zealandwaters. The greatest geographic source of new taxa is the islands and underwater features off northern New Zealand. The new shell-morphological term “sutsel” is introduced for the area between the SUTure and the SELenizone.